2016
DOI: 10.2320/matertrans.m2016035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nd or Zr Addition on Microstructure and Mechanical Properties of As-Cast Mg-Zn-Y Alloy

Abstract: The effects of Nd or Zr addition on microstructure and mechanical properties of casting Mg-Zn-RE alloy have been investigated. The results indicate that the optimum contents of Nd and Zr are 0.5% and 0.3% respectively. The less or higher contents all increase grain size and accelerate the formation of shrinkage porosity, and thus decrease tensile properties and change fracture regime from transgranular mode to intergranular mode during tensile tests. The Mg-Zn-RE ternary phases transform from W (Mg 3 Zn 3 (Nd,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…42 The quantity and distribution of intermetallics are closely correlated with mechanical properties. 43 The intermetallic morphology of ZK60 alloys with trace quantities of Cu changes, affecting the mechanical properties. Figure 15 shows the variations in the tensile properties and elongation to fracture of ZK60 alloys with various Cu concentrations under room temperature tensile conditions (E f ).…”
Section: Alloying Elements (Mg)mentioning
confidence: 99%
See 2 more Smart Citations
“…42 The quantity and distribution of intermetallics are closely correlated with mechanical properties. 43 The intermetallic morphology of ZK60 alloys with trace quantities of Cu changes, affecting the mechanical properties. Figure 15 shows the variations in the tensile properties and elongation to fracture of ZK60 alloys with various Cu concentrations under room temperature tensile conditions (E f ).…”
Section: Alloying Elements (Mg)mentioning
confidence: 99%
“…The quantity and distribution of intermetallics are closely correlated with mechanical properties . The intermetallic morphology of ZK60 alloys with trace quantities of Cu changes, affecting the mechanical properties.…”
Section: Magnesium’s Reaction To Various Alloying Elements (Mg)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indicating that fine grain strengthening does not play a leading role in improving mechanical properties, especially in ZA1210 alloy. It is well accepted that the mechanical properties of the alloy have an important relationship with the distribution, morphology, size and category of eutectic phase 18 . It is believed that the decrease of tensile properties of the Al-containing alloys can be explained by the following three aspects: (1) When the addition of Al exceeds 4%, with increasing of Al addition, the grains of the investigated alloys are gradually refined, but the primary α-Mg grains are almost surrounded by the coarsely and continuously interdendritic eutectic compounds, which can induce generation of the cracks and stress concentration at the interface between intermediate phase and matrix during deformation, thus leading to the deterioration of the tensile properties.…”
Section: Alloy Codementioning
confidence: 99%
“…[11][12][13] In Mg-Al-Zn magnesium alloys, adding minor titanium was found to effectively improve the mechanical properties at room temperature because of the refinement of the microstructure. [14][15][16][17][18][19] However, with the different alloying methods of titanium addition, investigation conducted by Yang et al 20 showed that adding different contents of titanium had no obvious effects on the tensile and creep properties of Mg-3Sn-2Sr alloy.…”
Section: Introductionmentioning
confidence: 99%